A comparison of two methods for estimating 50% of the maximal motor evoked potential. Issue 12 (December 2015) - Pitcher, Julia B.; Doeltgen, Sebastian H.; Goldsworthy, Mitchell R.; Schneider, Luke A.; Vallence, Ann-Maree; Smith, Ashleigh E.; Semmler, John G.; McDonnell, Michelle N.; Ridding, Michael C.
Highlights: Though desirable, it is often not feasible to construct corticomotor stimulus–response curves to set transcranial magnetic stimulation intensities. By analysing 176 corticomotor stimulus–response curves, we show that a motor evoked potential with amplitude 50% of maximum consistently occurs at 127–128% of resting motor threshold in healthy adults. A stimulus intensity adjusted to evoked a 1.0 mV MEP significantly underestimated this midpoint. Abstract: Objectives: Two commonly-used methods for setting stimulus intensities in transcranial magnetic brain stimulation studies were compared to determine which best approximated a motor evoked potential (MEP) of 50% of the maximal MEP amplitude (SI50 ); a suprathreshold intensity relative to resting motor threshold (rMT) or adjusting the intensity to evoke an MEP amplitude of 1 mV. Methods: Corticomotor stimulus–response curves and rMT for the right first dorsal interosseous (FDI) muscle of 176 subjects (aged 10–74 years) were retrospectively analysed. Results: Regardless of subject age or sex, SI50 occurred at 127.5 ± 11.3% rMT. Except in young children, MEPs of 1 mV were significantly smaller than those evoked at SI50 . Conclusions: In the inactive FDI muscle, a stimulus intensity of 127–128% rMT consistently gives the best approximation of SI50 in most subjects, except perhaps young children. Significance: Setting TMS stimulus intensities relative to rMT provides a less variable inter-subject comparator, with respect to individual differences in corticomotor input–output characteristics, than adjusting the stimulator output to give an absolute MEP magnitude.